Streaming video on a local area network (LAN): A case of corporate communication in FTMSK / Riaza Mohd Rias, Hayati Abdul Ghanny and Mohd Yunus Mohd Yussof - Mohd Rias, Riaza; Abdul Ghanny, Hayati; Mohd Yussof, Mohd Yunus (2005)
The streaming process means ensuring the received audio, motion video, and animation streams are smoothly rearranged to resemble the original stream, and thus be reproduced reliably (Fluckiger, 1995). Streaming of media files is perceived as a new tool to support and improve learning activities in academic environment. In order for streaming to work, the client side receiving the data must be able to collect the data and send it as a steady stream to the application that is processing the data and converting it to sound or pictures. This research discusses on the issues involoved in streaming live and on-demand video on FTMSK's LAN and to identify factors that affect the performance of video streaming in the faculty. The researh also discuss on the user acceptance of this new alternative of corporate communication in the faculty of IT and Quantitative Science and the challenges of implementing video streaming on a Local Area Network. The methods used for this study involves, experiments in the Hypermedia lab, and observation of the network performance and quality of the streaming video. Lastly, some suggestions are made to the faculty to have a better video streaming system implementation.